MARGINALIZATION OF DEPARTMENTS OF SOCIAL SCIENCES AND LANGUAGES IN SENIOR HIGH SCHOOL IN DENPASAR - Winaja, I Wayan (E-Journal of Cultural Studies, 2013)
Learning should be focused on the social and cultural development of intellectual ability, and encourage the learner’s comprehension and knowledge in order to produce intelligent and educated society. From the data collected from Public Senior High School 1 Denpasar and Dwijendra Senior High School Denpasar, it was found that the departments of social sciences and languages were seriously marginalized, indicated by the time allocated for social sciences and languages. The time allocated for Natural Sciences such as chemistry, physics, and biology averaged three hours a week. The additional ‘extra’ time allocated for Natural Sciences made the overall time allocated for them double the overall time allocated for Social Sciences such as economics, history sociology, and geography. Furthermore, the time allocated for one of them was one hour a week. The knowledge presented by the books of Natural Sciences was highly “instrumentalist-positivistic”; unlike the books of social sciences which only provided academic normative information. The modernity contained in “instrumentative positivism” was the philosophy which gave more priority to practical things and hard work with financial success as the main criterion. It was concluded that the marginalization of the departments of social sciences and languages in Public Senior High School 1 Denpasar and Dwijendra Senior High School Denpasar resulted from modernism, the culture of image, and the image that natural sciences were more advantageous than social sciences and languages.
Keywords: marginalization of social sciences and languages, senior high school, education.